Improving Textural and Catalytic Properties of Lanthanum-based Perovskite Catalysts for Automotive Exhaust Conversion - M. M., Yunus; I. D., Ibrahim; M. S, Shuwa (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
High cost, limited availability and low thermal stability of noble metals like Platinum, Palladium, Rhodium and Gold used in automotive exhaust emission control has prompted the search for a substitute catalyst with similar activity, better thermal stability and affordability. This work investigated the use of base metals catalysts such as Mn, Co, Ni and Fe to reduce the emission of harmful gases. Perovskites are mixed oxides that have a wide range of properties, such as electrical and magnetic. They are also used as catalysts for eliminating atmospheric pollutants. Silica-supported LaBO3 (B = Mn, Fe, Co, Ni) catalysts were synthesized by deposition-precipitation method, and calcined at high temperature of 8000C. Properties of the samples were investigated by scanning electron Microscopy-Energy Dispersive X-ray spectroscopy(SEM-EDX), FTIR, X-ray diffraction, Thermogravimetric analysis(TGA) and Brunauer-Emmett-Teller (BET) to survey the morphology and chemical composition, bulk structure, crystalline nature, surface area, thermal stability and porosity of the crystals. The crystallite sizes range between 25--41nm, and specific surface area of 16-- 219m2/g. LaNiO3/SiO2 presented the highest textural values (i.e. smallest crystallite size, highest specific surface area and pore volume) which are beneficial for high catalytic performance. It also exhibits better catalytic activity for oxidation of HC, CO and NO. At 3000C, the catalyst’s conversion efficiency, of the three exhaust gases, reaches more than 70%; which can be considered as a potential replacement for the expensive noble metal catalysts.